Dna Barcoding, Phylogenetic And Systematics Of Holothuroidea (Sea Cucumbers) In Malaysian Waters Based On 16s Rrna And Cytochrome Oxidase I (Coi) Genes - Ismail, Siti Hasmah (2013)
A morphological and molecular systematic study was conducted on family Holothuriidae, Stichopodidae, and also Caudinidae. They can be found in Malaysian waters. This is the first documentation of the Phylogenetic relationship and Barcoding systemic among Holothurians family and genera that integrates traditional classification and molecular techniques. The species investigated were divided into three families which is Family Stichopodidae, Holothuriidae and Family Caudinidae. In Family Stichopodidae, the species involved were Stichopus hermanni, S. ocellatus, Stichopus sp., S. chloronotus, S. monotuberculatus and S. rubermaculosus while for Family Holothuriidae, the family was divided into two genera which is genus Holothuria and Bohadschia. The Holothurian involved was Holothuria atra, H. edulis, H. coluber, H. hilla, H. leucospilota, H. flavomaculata and Pearsonathuria graffei while for the second genus was the genus Bohadschia which is B. argus, B. mormorata and B. bivittata. The last but no least family was the Family Caudinidae and the genus was Acaudina. The sample was Acaudina molpadiodes. A total of 53 samples consisting of 17 Holothuroidea species were sampled and measured to obtain the morphometric data. Brief morphometric measurement was done by classical taxonomy keys and comparison by photos as a support for molecular taxonomy. Overall, four characteristics were taken into consideration.